Analysis Techniques for the Power Spectral Density Estimation of Convolutionally Coded Impulse Radio UWB Signals Subject to Attenuation and Timing Jitter - Villarreal-Reyes, S.; Edwards, R.M. (IEEE transactions on vehicular technology, 2009)
A method for the spectral analysis of convolutionally coded Markov-driven impulse radio (IR)-based ultrawideband (UWB) systems is introduced. Example applications in UWB systems include the study of pulse position modulation (PPM), pulse-amplitude modulation (PAM), biorthogonal modulation, and pulse-shape modulation combined with periodic (e.g., pseudorandom)/random time-hopping (TH), as well as periodic/random direct-sequence (DS) multiplication. The effects of random jitter and pulse attenuation are considered in this analysis. The final result allows simple examination of the power spectral density (PSD) of such signals. This result clearly delimitates the relative contributions of parameters that allow enhanced design of UWB systems. Application examples are presented for a new convolutional encoder, providing a spectral-line-free PSD for quaternary biorthogonal (PAM/PPM) modulation IR UWB systems.